DISTRIBUTION ROUTE ANALYSIS WITH SAVING MATRIX METHOD IN DETERMINING HOT MIX ASPHALT (HMA) DISTRIBUTORS - Muhammad Fachry Hafid; Muhammad Dahlan; Nurhayati Rauf; Takdir Alisyahbana; Rahmaniah Malik (Center for Study and Journal Management FTI UMI, 2023)
The Gorontalo Regency Public Works Department is responsible for a road construction program, in this case, the Public Works Department will conduct project auctions from several existing road projects and there will be one contractor company that will get an auction, where the contractor will produce asphalt in one of the Asphalt companies. Mixing Plant (AMP). The asphalt distribution process of course has routes and distribution costs where this needs to be optimized to get efficient planning in the distribution process, in the project data of the Public Works Department in 2022 there are five road projects and in the Gorontalo Regency area there are five (5) Asphalt Mixing Plants ( AMPs). Distribution is one part of the activities of Supply Chain Management which distributes goods and services from producers to consumers. The idealism of distribution is to distribute or deliver the right amount and type of product at the right time and place at the lowest possible cost to generate maximum profit. The Vehicle Routing Problem (VRP) is related to determining the route for the problem of distributing goods or products involving more than one vehicle with a certain capacity to serve some customers with their respective requests. The results of this study found that the determination of the distribution route of hot mix asphalt with the saving matrix method found that, the Otopade-Liyoto Project (F1) with 1,639 Ton Asphalt Demand, the selected asphalt distributor was (F0-E) PT.PETRA with a distance of 14.4 Kilometers with a total cost of Rp42,508,800. Project (F2) road project Construction of the Buhu - Iloponu Perintis road with an asphalt demand of 609 tons, the selected asphalt distributor is (F0A) PT. Cahaya Nusa Sulutarindo with a distance of 9.6 Kilometers with a Total Cost of Rp 11,712,000. Project (F3) Pilomonu – Pasir Putih road with 763 Ton Asphalt Demand, the selected asphalt distributor is (F0-E) PT.PETRA with a distance of 38.1 Kilometers with a total cost of Rp52,806,600. Project (F4) of Molohu – Langge road with 656 Tons of Asphalt Demand, the selected asphalt distributor is (F0-E) PT.PETRA with a distance of 42.4 kilometers with a total cost of Rp 50,371,200. For the project (F5) of the Helume Bihe - Sukamaju road with an asphalt demand of 1,564 Tons, the selected asphalt distributor is (F0-E) PT.PETRA with a distance of 32.6 Kilometers with a total cost of Rp 92,127,600. Keywords: Distribution, Supply Chain Management, Vihicle Routing Problem, Asphalt Mixing Plant, Hot Mix Asphalt, Direct Shipment, Routes, Cost